Thực trạng học và dạy phát âm tiếng trung cho sinh viên năm thứ nhất và năm thứ hai ngành Ngôn ngữ Trung Quốc tại Trường Đại học Nông - Lâm Bắc Giang - Nguyễn , Thị Thanh Thủy; Hoàng , Như Hạnh; Ngô , Thị Hoàng Anh (Tạp chí Giáo dục, 2024)
Pronunciation is considered one of the fundamental and essential skills; however, it is also one of the most challenging skills to develop when enhancing foreign language proficiency. The study focuses on improving Chinese pronunciation skills for Chinese Language majors at Bac Giang Agriculture and Forestry University, particularly targeting first and second-year students, who are the primary recipients of pronunciation instruction. Data were collected from 116 students, 60 audio recordings, and 6 instructors teaching Chinese. The research findings have highlighted key issues in Chinese pronunciation and phonetics, the current situation of pronunciation teaching and learning, along with common pronunciation errors. Based on these results, the study suggests solutions to improve and enhance pronunciation skills, bringing significant effectiveness in students' learning and communication processes.